Analysis of Functional English Competency Needs of Primary School Teacher Education Students For Bilingual Learning - Sarjani, Tiarnita Maria; Sianipar, Revalina Angelila; Tarigan, Yobel; Simatupang, Christine Nathalia; Sitorus, Johana (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to analyze the readiness of Primary School Teacher Education (PGSD) graduates in facing bilingual school programs, specifically concerning functional English competency. Utilizing the Systematic Literature Review (SLR) method on journal articles published from 2017 to 2025 , the synthesis results indicate that the competency needs for bilingual primary school teachers extend beyond general language ability, centering on the mastery of Classroom English and English Pedagogical Content Knowledge (PCK) to support the CLIL (Content and Language Integrated Learning) approach. The identified gaps are that Primary School Teacher Education curricula tend to be less functionally oriented and are exacerbated by inconsistent linguistic modelling challenges in the academic environment. Therefore, the study recommends a reorientation of the Primary School Teacher Education curriculum towards explicit CLIL integration, an increase in minimum competency standards, and the development of practical Classroom English modules to bridge the gap and produce job-ready prospective bilingual teachers.